Research methods for criminal justice and criminology - Michael G. Maxfield (Wadsworth Thomson Learning, 2008)
One of my most oddly rewarding teaching experiences took place not in the classroom but on the streets of downtown Indianapolis. On my way to a meeting with staff from the Indiana Department of Correction, I recognized a student from the previous semester's research methods class